Linguistics and Legal Epistemology: Why the Law Pays Less Attention to Linguists Than It Should - Gary S. Lawson (Washington University Law Quarterly, 1995)
Law and linguistics ought to be natural partners. Modem statutory and constitutional interpretation' increasingly focuses on the generally accepted public meaning of legal language. Even persons who do not believe (as I do) that some form of public understanding of the relevant text is the endall, if not quite the be-all, of such interpretation are likely to regard the public understanding of statutory language as at least one relevant factor in legal interpretation. And who better than linguists to inform the law about the true facts regarding public usage and understanding of legal language? The law, however, is going to have a harder time accepting the help of linguists than it probably should.
Keywords: Linguistics